(3cTa GdCSQGQ YeG Naj Yf GdCacGQs - (3TgGH GdOjf CHh GdYHGS CMeO Hf YeGO GdOjf GdCabgSj,J (B808 (3g` s ((3eMeO GdebHhd Hf eMeO Hf CHj GdaJM Hf Jbi Hf YHO GdSdGe Hf eMeO GdcGfQhHi GdTGaYi GdeOfi s)
(3ChdgG (B:s
(3hHYO agPG cJGH CPcQ ajg CLhHI Yf eSGFd eTcdI hNajGJ Yf EOQGc MhGS GdbdhH hSejJg cJGH cTa GdCSQGQ YeG Nai Yf GdCacGQ s
(3BNQgG (B:s
(3Ydi CUfGa YHGOI GdYHjO hYHGOI GdCMQGQ hYHGOI GdJLGQ BNQ cJGH cTa GdCSQGQ YeG Nai Yf GdCacGQ s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1485s
(3eUOQ GbJfGA GdCUd (B:s
(3GdeJMa GdYQGbi (B_ (3HZOGO (B(1410) s
Keywords: (3Gdabg GdTGaYjs